Rancang Bangun Sistem Ground Control Station (GCS) Sebagai Sistem Kontrol Pada Traktor Pembajak Sawah - Estu Broto, Prasepvianto (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2025)
The Android-based GCS (Ground Control System) has been designed to operate the wireless prototype tractor. This research aims to design the GCS system as a controller for the prototype tractor. The research method employed is the sequential linear method. The conducted tests include data transmission time testing from the application, GPS testing, and prototype response testing. The testing involves comparing the command data transmission time from the application with the time it arrives at Firebase. Based on the obtained data, it can be seen that the data transmission speed and reception have no gaps. This is due to a stable network connection, enabling real-time communication between the application and Firebase. GPS testing is conducted to assess the accuracy of coordinate readings for determining the prototype's position. The prototype's position can be determined using the obtained coordinates, namely latitude and longitude, which are read from the GPS module installed on the device. The test results indicate a difference between the prototype's coordinate point (reference coordinate) and the coordinate point obtained from the timestamp application. The difference in coordinate readings between the prototype and the average plotted result is 0.2 meters. Prototype response testing is carried out to evaluate the device's responsiveness to commands from the control system on the smartphone. This test involves sending motion direction commands that the device needs to follow, followed by measuring how quickly the device responds to those motion commands. Based on the obtained data, the time required for the device to respond to the forward command provided is 01.61 seconds and 01.88 seconds. Keyword : Ground Control Station (GCS), Android, Waypoint, Wireless